2009
DOI: 10.1177/0748233708101594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subchronic methyl tert-butyl ether ether exposure on male Sprague-Dawley rats

Abstract: Methyl tert-butyl ether (MTBE) is an additive used to oxygenate gasoline to improve air quality by reducing tailpipe emissions of carbon monoxide and ozone precursors. Although several toxicity studies in rats have been conducted to examine the acute, subchronic, and chronic toxicities by employing various routes of exposure to MTBE, few data were available on the effects of MTBE exposure on blood. In this study, MTBE was administered to rats at dose levels of 0, 400, 800, and 1600 mg/kg/day, respectively. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…At the same time, there was no significant association between MTBE exposure and the prevalence of NAFLD separately in men and women ( p > 0.05, as shown in Table 2). Therefore, although the acute, subchronic, and chronic toxic effects of MTBE, such as lipid disorder [11], abnormal liver function [11], and oxidative stress [6,7,8], etc., were found in animal tests, there is no significant evidence showing an association between MTBE exposure and the prevalence of NAFLD in humans in our study. Of course, there were some limitations to this study, the first being that the exposure concentrations of MTBE among the subjects were relatively low (did not exceed the ACGIH TLV® of MTBE, 50 ppm); thus, it can hardly shed light on the association between relatively high exposure concentrations of MTBE and the prevalence of NAFLD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, there was no significant association between MTBE exposure and the prevalence of NAFLD separately in men and women ( p > 0.05, as shown in Table 2). Therefore, although the acute, subchronic, and chronic toxic effects of MTBE, such as lipid disorder [11], abnormal liver function [11], and oxidative stress [6,7,8], etc., were found in animal tests, there is no significant evidence showing an association between MTBE exposure and the prevalence of NAFLD in humans in our study. Of course, there were some limitations to this study, the first being that the exposure concentrations of MTBE among the subjects were relatively low (did not exceed the ACGIH TLV® of MTBE, 50 ppm); thus, it can hardly shed light on the association between relatively high exposure concentrations of MTBE and the prevalence of NAFLD.…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological investigation revealed that there was a significant positive correlation between ambient air concentrations and blood levels of MTBE [2,5]. The acute, subchronic, and chronic toxicities of MTBE have been explored, and the toxic effects of oxidative stress [6,7,8], DNA damage [5,6,7,8], DNA adducts [9,10], lipid disorder [11], abnormal liver functions [11], vascular lesions [12], and malignant tumors [13] induced by MTBE were found in animal tests. However, there is apparent uncertainty in the extrapolation of animal data to effects on humans [1,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports that MTBE causes leukemia, liver, kidney, and Leydig cells testicular tumors [4][5][6][7][8][9]. In addition, limited epidemiological and clinical examinations show that MTBE adversely affects human health, and causes several symptoms including aversion to the smell, headache, dizziness, nasal and ocular irritation when individuals are exposed to gasoline-containing MTBE [10][11][12].…”
Section: Introductionmentioning
confidence: 97%